Zlatorog Viktorja Parme - Pompe, Gregor (Muzikološki zbornik, 2009)
The article concentrates on the analysis of Parma's opera Goldenhorn, which occupied an important place in the composer's oeuvre as well as in the context of the development of the Slovenian opera.
Keywords: glasba; glasbena drama; music; opera; Parma, Victor: Zlatorog; Parma, Viktor, 1858-1924; Slovenia; Slovenija; vodilni motiv